The Kingdom of Fungi - Petersen, Jens H., 1956- (Book collections on Project MUSE., 2013)
"The fungi realm has been called the 'hidden kingdom, ' a mysterious world populated by microscopic spores, gigantic mushrooms and toadstools, and a host of other multicellular organisms ranging widely in color, size, and shape. The Kingdom of Fungi provides an intimate look at the world's astonishing variety of fungi species, from cup fungi and lichens to truffles and tooth fungi, clubs and corals, and jelly fungi and puffballs. This beautifully illustrated book features more than 800 stunning color photographs as well as a concise text that describes the biology and ecology of fungi, fungal morphology, where fungi grow, and human interactions with and uses of fungi"--Provided by publisher.